Experimental investigation of droplets on powder layer heated with temperature difference - Tan, Guan Yu (Nanyang Technological University, 2022)
Granular materials have been garnering attention over the course of the century. They come in a broad selection of shapes, sizes and are found in various natural and industrial applications. Even though studies have been conducted on different types of soils, powder, and granules. There has been growing attention toward microstructures and simulations. There are far more avenues of exploration that can be done to understand the complexity and interactions of granular materials due to the nature and powder-based industry applications that demands the study of droplets on heated powder bed with temperature difference. This project documents the behavior interactions when a liquid droplet is deposited on a heated powder bed with a temperature difference. The behavior can differ depending on the various conditions and parameters of the liquid and the powder bed. Analytical descriptions were noted down based on the difference in interactions. Initial observations were conducted by dispensing small ethanol droplet onto different powder bed thickness with a variation of temperature set by the heater. Phase diagrams for ethanol droplets were created to determine three distinct phases observed. The experiment proceeds to investigate whether the temperature gradient is influenced by the contact area. The experiment was extended to investigate the various physical properties of fluid such as surface tension, viscosity, specific heat, and boiling point to understand the factors which affect the droplet behavior. The experiment furthers the study on how thin powder bed thickness will have a relation to the effect of temperature difference. This study has added new insights to achieve better understanding to improve in printing processes of temperature different powder bed.